PENGGUNAAN BAKTERI PROBIOTIK SEBAGAI BAHAN PAKAN DALAM BUDI DAYA SIDAT (Anguilla sp) FASE GLASS EEL - Tiara Dewanti P.S, - (2018)
Budi dayasidat (Anguilla sp) merupakansalahsatupeluangusaha yang potensialuntukdikembangkan di negara Indonesia.Kegiatanbudidayasidatinimemilikikendala yang menghambatproduksisidatdiantaranyapertumbuhansidat yang lambatdanpenurunanproduksi yang disebabkanolehberkembangnya bakteri patogen.Lajupertumbuhansidatperluditingkatkandenganmenambahkanprobiotikpadapakansidatsebagaibahanpembenahpertumbuhansidat.Penelitianinibertujuanuntukmengetahuipengaruhpenggunaanprobiotikdengandosis yangberbedapadapakanterhadaplajupertumbuhansidatselamapemeliharaan.Metodepenelitian yang digunakanadalahmetodeeksperimentaldenganteknikpurposive sampling danrandom sampling without replacement.Pemberiandosisprobiotikdilakukansebanyak 3 perlakuanyaitudosissebesar 0% (Kontrol), 5% (5 ml/ 100gr) dan 10% (10 ml / 100gr)dengan 3 kali pengulangan. Sidatfaseglass eel ditebarkankedalamakuariumberukuran 30x30x40 cm dengankepadatan 50 ekor / akuarium. Parameter yang diamatimeliputilajupertumbuhanspesifik,kelangsunganhidup, rasiokonversipakan, efisiensipemanfaatanpakandan parameter kualitas air.Data dianalisisdenganragam ANOVA,dilanjutkandenganuji Tukey untukmenentukanperbedaanantarperlakuan.Hasilpenelitianmenunjukkanbahwapemberianprobiotiktidakmemberikanpengaruhnyataterhadaplajupertumbuhanspesifikbobotikan, rasiokonversipakanmaupunefisiensipemanfaatanpakan, namunmemberikanpengaruhnyataterhadaplajupertumbuhanspesifikpadapanjangdantingkatkelangsunganhidup,. Konsentrasiprobiotikdengandosis 10% menghasilkanpertumbuhanpanjangdantingkatkelangsunganhiduptertinggimasing-masingsebesar 1,33 cm dan 74%.Sehinggakonsentrasiprobiotik yang baikunutkmeningkatkanlajupertumbuhansidatadalahdosisprobiotik 10% (10 ml/100 gr);---Eels cultivation (Anguilla sp.) is one of the potential business opportunities to be developed in Indonesia. The cultivation of eels has the late growth and Fish production is hampered due to the development of pathogenic bacteria. One of the solutions to accelerate the growth rate is by adding probiotic bacteria as feed for improvenment of fish growth. The objective of this research was to know the effect of addition probiotic bacteria in eels feed on the best of growth of Anguilla spp. in the cultivation. In this research, probiotic bacteria was introduced in diet at three different dosages of probiotic ( P0: without probiotic, P1:5% and P2: 10%) with 3 replications. The research method used an experimental methode with purposive sampling and random sampling without replacement technique.Glass eel of 50 individuals were cultivated in the aquarium with size 30x30x40 cm. The parameters observed were Growth rate, survival rate (SR),FeedConvertion Ratio (FCR), efficiency of feed utilization and water quality. Data were analyzed by ANOVA followed by W-Tukey Test. The results showed the addition of probiotic bacteria with various concentrations into the feed was not significant (p>0,05) on the specific growth rate of weight, feed convertion ratio and efficiency of feed utilization, but have higher significant influenced (P<0,05) on the the specific growth rate of length and survival rate. The treatment P2 (10 % of probiotoic) produces the highest length of 1.33 cm and survival rate of 74%, and the treatment P2 (10 % of probiotoic) showed the best one treatment dosage for glass eels growth rate than the other treatments.